2021
DOI: 10.1002/er.7136
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation, thermal conductivity, and phase change tests of the cement‐hyperbranched poly amino‐ester‐block‐poly cabrolactone‐polyurathane plaster‐lead oxide and arsenic oxide composite for development of radiation shielding material

Abstract: Summary The work which has been done on cement‐polymer composite based shielding materials was comprehensively described in the present article, the choice of the study presented here is based on the choice of the researches. The new Hyperbranched Poly Amino‐Ester‐block‐Poly Caprolactone‐Polyurathane Plaster‐concrete composites mixed with different percentage soft lead oxide and arsenic oxide is used to research gamma‐ray shielding and thermal conductivity characteristics. The synthesis of new Hyperbranched Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…It should also be noted that when the gamma radiation energy increases, the RPE rates decrease, meaning that these decreases in the RPE rates confirm that all of our results are compatible with the other attenuation parameters (i.e., , , HVL, TVL, MFP) computed and experimentally detected. These conclusions obtained are consistent with the results of the research composites developed for gamma-ray shielding with various nanostructured additives, including polymers [ 11 , 12 , 30 , 31 , 32 , 33 ]. As a result, the current alterations in nanoparticle proportions are quite efficacious for diminishing the influence of gamma radiation.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It should also be noted that when the gamma radiation energy increases, the RPE rates decrease, meaning that these decreases in the RPE rates confirm that all of our results are compatible with the other attenuation parameters (i.e., , , HVL, TVL, MFP) computed and experimentally detected. These conclusions obtained are consistent with the results of the research composites developed for gamma-ray shielding with various nanostructured additives, including polymers [ 11 , 12 , 30 , 31 , 32 , 33 ]. As a result, the current alterations in nanoparticle proportions are quite efficacious for diminishing the influence of gamma radiation.…”
Section: Resultssupporting
confidence: 90%
“…Protection from the effects of radiation includes two conditions: protection under normal and abnormal conditions. Under normal conditions, the impermeability of radioactive and radiation-containing materials is the main objective, while under abnormal conditions, the flexibility, durability, high corrosion resistance, and thermal properties of the materials are taken into account, in addition to the former [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was related to the reduced Tm of the PS-PEG/BN. Additionally, the interactions between the filler and the matrix decreased the free volume of the polymer chain [35,42].…”
Section: Dsc Results Of the Ps-peg/bn/pbo Pcm Nanocompositesmentioning
confidence: 99%
“…In terms of developing the properties needed in structures, these behaviors bring polymers to an important point in multidisciplinary scientific research [33,34]. In the study of Cinan et al, the radiation absorption parameters-the theoretical calculations, the thermal conductivity, the morphological analysis, Tm, Tc, ΔHm, and ΔHc of Portland Cement-HB(PAE-b-PCL)-PU plaster and HB(PAE-b-PCL)-PU/PbO-BN nanocomposites were investigated [35]. When HB(PAE-b-PCL) PU plaster, PbO, and AsO were added to Portland Cement, we found that it increased the properties of the cement as a radiation shielding material and the thermal conductivity values.…”
Section: Introductionmentioning
confidence: 99%